The Effect That an Integrated Classroom of Both Autistic and Non-Autistic Children has on the Development of the Social Skills of Autistic Children: An Exploratory Study of a Sample of Autistic Children from Al-Hid Primary Boys School (The International Journal for Scientific Research, 2024)
This study aimed to investigate the effect of using the peer integration strategy in developing social skills in autistic children, by answering the following main question: What is the effect of using the peer integration strategy in developing social skills in autistic children?To answer the main study question included in the context of this study, the researcher in this study followed the quasi-experimental approach that relies on studying the phenomenon as it exists in reality, and is based in its original construction on experimental application; to obtain data from its primary sources through a questionnaire that was designed according to the scientific steps approved in this regard, as it was applied to the study community consisting of all autism students registered in government schools in the Kingdom of Bahrain in the academic year 2022/2023 AD, numbering (106) male and female students according to official statistics issued by the Ministry of Education in the Kingdom of Bahrain. By selecting (5) autism students registered at Al-Hadd Elementary School for Boys in the academic year 2022/2023, with mild and moderate autism, and selecting (5) normal students to play the role of peers, as they were chosen by classroom teachers and subject teachers based on their personal qualities that qualify them to play the role of peers, their high academic level, their activity in school committees and teams, in addition to their personal desire to support the autism class as a deliberate sample for the study. This school was chosen because the researcher works as an assistant director in it, which made it easy for her to implement the experiment easily and smoothly, as well as bypassing many of the administrative matters required by this type of field applications. After ensuring that the study tools met their psychometric characteristics, they were applied to the target sample, and statistical analysis was conducted to extract the results. The results of the study concluded that the performance of the study individuals on the post-measurement items was better than their performance on the pre-measurement items, as the arithmetic mean of their scores on the post-measurement items was (2.72) with a standard deviation of (0.09), while the mean scores of the study individuals after applying the experiment to them on the pre-measurement items was (2.48) with a standard deviation of (0.06). The results of the study also showed that the calculated value of (z) indicates the presence of statistically significant differences at a significance level (@=0.05) in the average scores of the study members related to the effectiveness of the training program in developing social skills in children on the pre- and post-measurement items, meaning that the applied training program affected the performance of the study members.In light of the results reached by the study, it recommends working on training families of autistic children through workshops and training courses and involving them in the design and implementation of educational programs. As well as training autistic children on social skills at an early age to help them rely on themselves in their daily lives.
Keywords: Social Skills; Peer Integration; Autism